(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
This paper offers a preliminary overview on the large fossil mammals (Primates, Hyaenidae, Proboscidea, Rhinocerotidae, Equidae, Hippopotamidae, Suidae, Giraffidae, and Bovidae) from the Early Pleistocene sedimentary succession of the Dandiero (Buia) Basin (Danakil Depression, Eritrea). The 1995-1997 Eritrean-italian fossil collection has been revised and studied. A few significant remains collected during the 2002-2004 field activities have also been included. Eighteen species of mammals have been identified, described and illustrated in the principal specimens. The systematic study allows general coclusions on the biochronologic and paleoenvironmental significance of the faunal assemblage. This study is completed by an analysis of “Genus Faunal Resemblance Index” (GFRI) with some well known faunal assemblages of Africa across the time span Late Pliocene – Middle Pleistocene.